Pengaruh Pelayanan Karyawan Dan Program Maskapai Penerbangan Terhadap Kepuasan Konsumen Pada PT Sriwijaya Air Makassar - Rahmad Wijaya; Nasriah Akil; Fauziah Fauziah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The aim of this research is to determine the partial and simultaneous influence of employee service variables, airline programs, customer satisfaction, where this research uses a quantitative research approach with a sample size of 100 PT consumers. Sriwijaya Air using the multiple regression analysis method with the help of the SPSS.26 application. The findings of this research show that the employee service variable has a positive and significant effect on customer satisfaction, the work program variable also has a positive and significant effect on customer satisfaction, while simultaneous testing shows that employee service and airline programs have a positive and significant effect on customer satisfaction at PT. Sriwijaya Air.